Constitutional Guarantees Regional Regulations of Sharia in Indonesia - Sodikin Sodikin (Kanun Jurnal Ilmu Hukum, 2021)
Regional regulations or Sharia Regional Regulations are the product of legislation under laws that have Islamic teachings. The problem that underlies the existence of a Sharia Regional Regulations is whether it is constitutionally justified and how the constitutional guarantee of the existence of a Sharia Regional Regulations is applicable. This problem is examined using descriptive normative research methods with qualitative analysis. The results of this study indicate the objectives achieved are first, the existence of Sharia Regional Regulations due to the legal awareness of people who are aware as religious citizens so that their lives will be better which is constitutionally justified in the 1945 Constitution and Pancasila. Second, Article 29 of the 1945 Constitution and Pancasila provides constitutional guarantees for the existence of Sharia Regional Regulations. This is because Chapter XI Article 29 of the 1945 Constitution regulates the issue of Religion which is strengthened by the First Precepts of the Pancasila which shows the constitutional rights of citizens, that is, every citizen has the right and obligation to have a religion and practice his religion and beliefs.